Impact of carbon source and COD/N on the concurrent operation of partial denitrification and anammox. (30th January 2019) - Le, Tri; Peng, Bo; Su, Chunyang; Massoudieh, Arash; Torrents, Alba; Al‐Omari, Ahmed; Murthy, Sudhir; Wett, Bernhard; Chandran, Kartik; DeBarbadillo, Christine; Bott, Charles; De Clippeleir, Haydée
Abstract: In this study, concurrent operation of anammox and partial denitrification within a nonacclimated mixed culture system was proposed. The impact of carbon sources (acetate, glycerol, methanol, and ethanol) and COD/NO3 − ‐N ratio on partial denitrification selection under both short‐ and long‐term operations was investigated. Results from short‐term testing showed that all carbon sources supported partial denitrification. However, acetate and glycerol were preferred due to their display of efficient partial denitrification selection, which may be related to their different electron transport pathways in comparison with methanol. Long‐term operation confirmed results of batch tests by showing the contribution of partial denitrification to nitrate removal above 90% after acclimation in both acetate and glycerol reactors. In contrast, methanol showed challenges of maintaining efficient partial denitrification. COD/NO3 − ‐N ratio mainly controlled the rate of nitrate reduction and not directly partial denitrification selection; thus, it should be used to balance between denitrification rate and anammox rate. Practitioner points: The authors aimed to investigate the impact of carbon sources and COD/NO3‐N ratio on partial denitrification selection. All the carbon sources supported partial denitrification as long as the nitrite sink was available. 90% partial denitrification could be achieved with both acetate and glycerol in long‐term operations. COD/NO3‐N ratio did not directly control partial denitrification but can be used to balance between denitrification rate and anammox rate.